Furacin Ointment for Local Treatment of Burns - S. V. Nadkarni; M. N. Nayak; T. K. Malik; S. K. Parashar; R. A. Varma (Indian Journal of Plastic Surgery)
Furacin Ointment is one of the drugs used for the local wounds of burns but has not been clinically assessed in India, so far. This is a review of the clinical trial of the drug conducted in the general hospital setup. 71 cases were ftreated with Furacin Ointment applied locally twice a week. 32 were superficial burns and 39 were deep burns. The data of incidence, causes, the percentage of body surface burnt etc. are presented, as also the results of the treatment, as judged by the average hospital stay, and skin-graft take. The hospital stay was markedly less as compared with those who were treated on other lines of local treatment. Considering 809 take of the graft as successful 70% had good results, after skin-grafting. Detailed bacteriological study was also carried out, and the relevant data is presented.